Longitudinal SARS-CoV-2 humoral response in MS patients with and without SARS-CoV-2 infection prior to vaccination - van Dam, Koos P. J.; Hogenboom, Laura; Stalman, Eileen W.; Kummer, Laura Y. L.; Steenhuis, Maurice; Keijser, Jim B. D.; Brinke, Anja ten; van Ham, S. Marieke; Kuijpers, Taco W.; Rispens, Theo; Wieske, Luuk; Eftimov, Filip; et al. (Frontiers in Neurology, 2022)
Introduction: During the COVID-19 pandemic, certain disease modifying therapies (DMTs) used in multiple sclerosis (MS), such as anti-CD20 therapies, have been associated with decreased humoral responses after SARS-CoV-2 vaccination. Hybrid immunity, referring to immunity after both vaccination and SARS-CoV-2 infection, might increase humoral responses. Methods: This was a substudy of two prospective cohort studies on SARS-CoV-2 antibodies after SARS-CoV-2 infection and vaccination. RBD-specific IgG titers of patients with MS and healthy controls who had experienced SARS-CoV-2 infection prior to first vaccination were compared to those in patients and healthy controls without prior infection. Humoral responses were measured at various time points after SARS-CoV-2 infection in convalescent patients and in all patients prior to first vaccination, 28 days after first vaccination and 28 days after second vaccination. Results: 102 individuals (of which 34 MS patients with DMTs (natalizumab or ocrelizumab), 30 without DMTs and 38 healthy controls) were included. 51 of these individuals were convalescent. Median SARS-CoV-2 antibody titers were higher after first vaccination in convalescent individuals compared to individuals without infection prior to vaccination. SARS-CoV-2 antibody titers were comparable after second vaccination in MS patients with and without prior infection. However, in the convalescent ocrelizumab treated patients, SARS-CoV-2 antibody titers did not increase after vaccinations. Conclusion: In patients with MS without anti-CD20 therapies, SARS-CoV-2 infection before vaccination increases humoral responses after the first vaccination, similar to healthy controls. In MS patients treated with ocrelizumab (convalescent and non-convalescent), humoral responses remained low.